AN ANALYSIS OF BUYA HAMKA’S THOUGHTS ON ADAB CRISIS SOLUTION THROUGH HIKMAH METHODS ACCORDING TO TAFSIR AL-AZHAR - Islam, Muhammad Thoriqul; Marjany, Nawa Marjany (Khatulistiwa, 2025)
Courtesy or adab is crucial in human life because it will influence many other aspects of life. The current courtesy crisis is vital to overcome to create civilized people. One of the solutions to the courtesy crisis is wisdom (hikmah). This research analyzed Buya Hamka’s thoughts on solutions to the courtesy crisis through the wisdom method. The research employed a literature study method with a content analysis approach. Data was obtained from Buya Hamka’s works and books and journals related to Buya Hamka’s thoughts. Data analysis used three steps: compare, contrast, and criticize. The research revealed that Hamka defined wisdom as a harmony of interrelated meanings, where achieving wisdom was the main goal for those who attempted to learn it. Hamka offers several ways to gain wisdom, i.e., reading and understanding the Qur’an, thinking deeply, and imitating good behavior. The goals of wisdom include being wise in carrying out obligations, knowing the nature of things/the secrets of life, being able to adjust actions and knowledge, knowing God, and achieving happiness. According to Hamka, wisdom can solve the courtesy crisis by maximizing seven aspects of spiritual intelligence: al-ruh, al-qalb, al-nafs, al-aql, faith, worship, and courtesy. Spiritual intelligence is vital for maintaining mental health, ultimately forming a civilized person.Courtesy or adab is crucial in human life because it will influence many other aspects of life. The current courtesy crisis is vital to overcome to create civilized people. One of the solutions to the courtesy crisis is wisdom (hikmah). This research analyzed Buya Hamka’s thoughts on solutions to the courtesy crisis through the wisdom method. The research employed a literature study method with a content analysis approach. Data was obtained from Buya Hamka’s works and books and journals related to Buya Hamka’s thoughts. Data analysis used three steps: compare, contrast, and criticize. The research revealed that Hamka defined wisdom as a harmony of interrelated meanings, where achieving wisdom was the main goal for those who attempted to learn it. Hamka offers several ways to gain wisdom, i.e., reading and understanding the Qur’an, thinking deeply, and imitating good behavior. The goals of wisdom include being wise in carrying out obligations, knowing the nature of things/the secrets of life, being able to adjust actions and knowledge, knowing God, and achieving happiness. According to Hamka, wisdom can solve the courtesy crisis by maximizing seven aspects of spiritual intelligence: al-ruh, al-qalb, al-nafs, al-aql, faith, worship, and courtesy. Spiritual intelligence is vital for maintaining mental health, ultimately forming a civilized person.